The role of leasing companies in the economy of the Russian Federation - V. A. Dyakonova; N. B. Ershova (Вестник университета, 2019)
Increased production and investment in order to meet growing demand are necessary for the sustainable development of the economy. Leasing, as a tool, can significantly help in the implementation of these tasks. It is a signifi factor in economic growth, contributing to an increase in the production volume of goods and services through the creation of new production capacities and the attraction of investment resources. A comparative characteristic of leasing in Russia and other countries of the world has been introduced in the article, the current situation on the Russian market and its expected development in the future is described, the diff rences between leasing and rental relationship have been revealed.